Giant rubber-like behavior induced by martensite aging in Ni51Fe18Ga27Co4 single crystals. (15th March 2019) - Panchenko, E.; Timofeeva, E.; Eftifeeva, A.; Osipovich, K.; Surikov, N.; Chumlyakov, Y.; Gerstein, G.; Maier, H.J.
Abstract: Stress-induced martensite aging along the [110]B2 ||[100]L10 -direction in compression was employed to enhance the functional properties of Ni51 Fe18 Ga27 Co4 single crystals. Stress-induced martensite aging induces two effects. Firstly, a two-way shape memory effect with a reversible compressive strain of −4.3% along the [110]В2 direction and a reversible tensile strain of +9.0% along the normal [001]B2 -direction. Secondly, rubber-like behavior with giant reversible compression strain up to −15.0% along the [100]B2 -direction caused by L10 -martensite variant reorientation was observed. This exceeds the maximum compressive transformation strain (−6.3%) during the B2-L10 martensitic transformation by a factor of two. Graphical abstract: Unlabelled Image